Breast cancer. Conservative treatment.: preliminary communication - Sabini, Graciela; Musé, Ignacio; Notejane, Roberto; Viola, Alberto; Pees, Graciela (Cirugía del Uruguay, 1989)
45 cases of breast cancer, stages I and 11, treated with conservative procedures are analysed. Patients were selected from a group of 894 cases derived from the ara of socialized medicine, assisted and controlled by the same medical group in a period of up to 8 years.